2008
DOI: 10.1002/anie.200704972
|View full text |Cite
|
Sign up to set email alerts
|

Tripeptides as Efficient Asymmetric Catalysts for 1,4‐Addition Reactions of Aldehydes to Nitroolefins–A Rational Approach

Abstract: Bridging the gap: Conformational analysis of a peptidic catalyst for aldol reactions led to the development of H‐D‐Pro‐Pro‐Asp‐NH2 as a highly efficient catalyst for conjugate addition reactions between aldehydes and nitroolefins (see scheme). Only 1 mol % of catalyst suffices to obtain γ‐nitroaldehydes in excellent yields and stereoselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
78
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(84 citation statements)
references
References 68 publications
0
78
0
2
Order By: Relevance
“…Whereas small rigid organocatalysts offer only a limited number of sites for structural and functional diversity, peptides have a modular nature, which allows the creation of optimized catalysts. large number of peptidic catalysts have been designed [37], and it has been shown that N-terminal prolyl-peptides efficiently catalyze reactions proceeding via enamine intermediates [38]. Earlier, we reported the first continuous-flow approach for the selective asymmetric synthesis of -nitroaldehydes, utilizing solid supported peptidic catalysts readily synthesized and immobilized in a single step [39].…”
Section: Peptide Catalyzed Stereoselective Reactions In a Continuous-mentioning
confidence: 98%
“…Whereas small rigid organocatalysts offer only a limited number of sites for structural and functional diversity, peptides have a modular nature, which allows the creation of optimized catalysts. large number of peptidic catalysts have been designed [37], and it has been shown that N-terminal prolyl-peptides efficiently catalyze reactions proceeding via enamine intermediates [38]. Earlier, we reported the first continuous-flow approach for the selective asymmetric synthesis of -nitroaldehydes, utilizing solid supported peptidic catalysts readily synthesized and immobilized in a single step [39].…”
Section: Peptide Catalyzed Stereoselective Reactions In a Continuous-mentioning
confidence: 98%
“…A variety of strategies have been explored for de novo construction of modular catalysts that enable chemical selectivity, regioselectivity, or enantioselectivity as a consequence of their structural organization. For example, synthetic peptides equipped with catalytic artificial amino acid groups or transition metal sites have been demonstrated to be effective enantioselective catalysts due to the proximity of the catalytic sites to the asymmetric environment created by their backbone (2)(3)(4). Similarly, it has been reported that nucleic acids can be used as chiral scaffolds for asymmetric synthesis and catalysis (5,6).…”
mentioning
confidence: 99%
“…Initially, the peptide H-D-Pro-Pro-Asp-NHresin was employed, immobilized on PS-MBHA resin with a loading of 0.64 mmol g -1 (catalyst 58). 131 For the CF reactions, 150 mg of the heterogeneous catalyst was incorporated into a stainless steel cartridge with internal dimensions of 70×4 mm. To provide accessibility of the immobilized catalyst molecules, the matrix of the supporting polymer should be swollen.…”
Section: Cf Organocatalytic Conjugate Additions 4311 Cf Methods Dementioning
confidence: 99%
“…The supported peptidic catalyst was obtained in a TFA salt form after the SPPS, and the effect of a basic additive was next examined to promote the liberation of the N-terminal secondary amine and maybe facilitate catalysis. 129 On the basis of literature data, Nmethylmorpholine (NMM) was chosen as base, 131 and the effects of different amounts of NMM were then investigated under the previously optimized CF reaction conditions. It emerged that the diastereoselectivity decreased dramatically upon addition of the base, whereas the yield and enantioselectivity remained intact (Table 9).…”
mentioning
confidence: 99%
See 1 more Smart Citation